Mapping the brain's metaphor circuitry: metaphorical thought in everyday reason - Lakoff, George (Frontiers in Human Neuroscience, 2014)
An overview of the basics of metaphorical thought and language from the perspective of Neurocognition, the integrated interdisciplinary study of how conceptual thought and language work in the brain. The paper outlines a theory of metaphor circuitry and discusses how everyday reason makes use of embodied metaphor circuitry.